2006
DOI: 10.1055/s-2006-950174
|View full text |Cite
|
Sign up to set email alerts
|

“Shades of Beauty”: Examining the Relationship of Skin Color to Perceptions of Physical Attractiveness

Abstract: The purpose of this research project was to investigate the relationship between skin color and level of perceived physical attractiveness. Previous research suggested that skin color plays an important role in how we perceive an individual's physical attractiveness. The current study was conducted to determine how influential the role of race is on perceptions of physical attractiveness. In this study, 79 subjects were asked to evaluate images of potential endorsers to be used in an upcoming advertising campa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 3 publications
1
19
0
2
Order By: Relevance
“…Skin color and skin tone is commonly used in determining a person's race or ethnicity (Jablonski & Chaplin, 2000). In modern days, skin tone is also used as an indicator of one's social, cultural and class location (Hall, 1997), as well as physical attractiveness (Frisby, 2006). Beauty is traditionally associated with women and femininity, and skin tone has been an important sexual attribute of women (Frost, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Skin color and skin tone is commonly used in determining a person's race or ethnicity (Jablonski & Chaplin, 2000). In modern days, skin tone is also used as an indicator of one's social, cultural and class location (Hall, 1997), as well as physical attractiveness (Frisby, 2006). Beauty is traditionally associated with women and femininity, and skin tone has been an important sexual attribute of women (Frost, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Across ethnic groups, however, the picture is complicated by the legacy of colonialism and racism in some societies, which has typically meant a denigration of darker skin tones and an association between fairness of skin with goodness and power (see Hall, 1995; Russell, Wilson & Hall, 1992; Swami, 2007). Thus, a number of studies have shown that dark‐toned individuals face more discrimination than individuals with light‐toned skin (Frisby, 2006; Keenan, 1996; Leslie, 1995), and that European (Caucasoid) features are accorded higher status, even within some minority ethnic groups (Maddox, 2004; Thompson & Keith, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…More appealing individual were more inclined to be connected with characteristics which is positive. Hence, less appealing of individuals are more inclined to be associated with negative ones (Frisby, 2006).Generally, physical appearance specifically the skin have an impact to both men and women with their social relations.…”
Section: Discussionmentioning
confidence: 99%